2015
DOI: 10.1259/bjr.20150191
|View full text |Cite
|
Sign up to set email alerts
|

Radiological interpretation of images displayed on tablet computers: a systematic review

Abstract: Objective: To review the published evidence and to determine if radiological diagnostic accuracy is compromised when images are displayed on a tablet computer and thereby inform practice on using tablet computers for radiological interpretation by on-call radiologists. Methods: We searched the PubMed and EMBASE databases for studies on the diagnostic accuracy or diagnostic reliability of images interpreted on tablet computers. Studies were screened for inclusion based on predetermined inclusion and exclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Promisingly, in radiology and echocardiography where practice is in essence based on image analysis, recent studies demonstrate that experts can accurately diagnose images on tablets. 11 12 Further, an additional study from the radiological field reveals that experts' subjective evaluation of the quality of radiological images is as positive for tablets as for computer screens. 13 The evidence is promising regarding the usability of handheld devices (smartphones and tablets) for expert teleconsultation.…”
Section: Introductionmentioning
confidence: 99%
“…Promisingly, in radiology and echocardiography where practice is in essence based on image analysis, recent studies demonstrate that experts can accurately diagnose images on tablets. 11 12 Further, an additional study from the radiological field reveals that experts' subjective evaluation of the quality of radiological images is as positive for tablets as for computer screens. 13 The evidence is promising regarding the usability of handheld devices (smartphones and tablets) for expert teleconsultation.…”
Section: Introductionmentioning
confidence: 99%
“…The number of mobile apps for displaying radiology exams continues to expand, with 11 image viewing apps available for download according to a recent review [13]. In a separate review by Caffery et al, 11 recent publications have evaluated the diagnostic accuracy of reading radiologic exams on tablet computers with comparison to standard workstations [14]. Ten of these used the iPad, as in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…[1][2][3][4][5] A recent review found that there were no significant differences in the diagnostic accuracy between the iPad and digital imaging and communication in medicine (DICOM)-calibrated control displays. 6 The US Food and Drug Administration have cleared the use of the iPad for primary radiological diagnosis. 7 However, the clearance is limited to small-matrix images and situations where there is no access to a primary diagnostic display.…”
Section: Introductionmentioning
confidence: 99%